Food chemistry /H.-D. Belitz, W. Grosch, P. Schieberle - Belitz, H.-D
For more than two decades, this work has remained the leading advanced textbook and easy-to-use reference on food chemistry and technology. Its fourth edition has been extensively re-written and enlarged, now also covering topics such as BSE detection or acrylamide. Food allergies, alcoholic drinks, or phystosterols are now treated more extensively. This provides student and researchers in food science, food technology, agricultural chemistry and nutrition with in-depth insight into food chemistry and technology. They also make the book a valuable on-the-job reference for chemists, food chemists, food technologists, engineers, biochemists, nutritionists, and analytical chemists in food and agricultural research, food industry, nutrition, food control, and service laboratories.